2016
DOI: 10.1038/srep24409
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning of macrophage activation using synthetic rocaglate derivatives

Abstract: Drug-resistant bacteria represent a significant global threat. Given the dearth of new antibiotics, host-directed therapies (HDTs) are especially desirable. As IFN-gamma (IFNγ) plays a central role in host resistance to intracellular bacteria, including Mycobacterium tuberculosis, we searched for small molecules to augment the IFNγ response in macrophages. Using an interferon-inducible nuclear protein Ipr1 as a biomarker of macrophage activation, we performed a high-throughput screen and identified molecules t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 65 publications
5
19
0
Order By: Relevance
“…Our studies extend those of Bhattacharya et al (50) in documenting an antiinflammatory response by rocaglates. Importantly, we demonstrate that CR-1-31B, and related rocaglates, can be used to interdict this process in the brain, highlighting its potential use as an antimalarial drug for intervention in CM in humans.…”
Section: Discussionsupporting
confidence: 91%
“…Our studies extend those of Bhattacharya et al (50) in documenting an antiinflammatory response by rocaglates. Importantly, we demonstrate that CR-1-31B, and related rocaglates, can be used to interdict this process in the brain, highlighting its potential use as an antimalarial drug for intervention in CM in humans.…”
Section: Discussionsupporting
confidence: 91%
“…Taken together these data demonstrate that macrophage activation by rocaglates is proportional to their translation inhibition activity. Importantly, general translational inhibitors, such as cycloheximide and puromycin, do not cause IRF1 co-stimulation, as described in our previous studies (15).…”
Section: Macrophage Activation By Rocaglates Is Coupled To Partial Trsupporting
confidence: 71%
“…Screening small molecule libraries, we found several synthetic rocaglates that potentiated pleiotropic effects of IFNγ on primary macrophages (15). Rocaglates are a class of bioactive derivatives of natural products isolated from medicinal plants of the Aglaia species that have been used in traditional Chinese medicine for treatment of fever, cough, diarrhea and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl rocaglate ( 4 ) was found to be a specific inhibitor of TNFα-R or PMA-induced NF-κB activity in T cell lines [4,5][9-13] and rocaglamide was recently reported to inhibit cancer cell migration through Rho GTPase inhibition [14]. In a collaboration with Kramnik and co-workers, we found that the synthetic rocaglate derivatives ( 3 and 4 ) synergized with low concentrations of IFNγ in primary macrophages to stimulate expression of some IFN-inducible genes, including a key regulatory factor, Irf1, which activates autophagy [15]. …”
Section: Introductionmentioning
confidence: 99%